Can Robotic Gastrectomy Surpass Laparoscopic Gastrectomy by Acquiring Long-Term Experience? A Propensity Score Analysis of a 7-Year Experience at a Single Institution - Hong, Sung-Soo; Son, Sang-Yong; Shin, Ho-Jung; Cui, Long-Hai; Hur, Hoon; Han, Sang-Uk (Journal of gastric cancer, 2016)
It is hypothesized that robotic gastrectomy may surpass laparoscopic gastrectomy after the operators acquire long-term experience and skills in the manipulation of robotic arms. This study aimed to evaluate the long-term learning curve of robotic distal gastrectomy (RDG) for gastric cancer compared with laparoscopic distal gastrectomy (LDG). From October 2008 to December 2015, patients who underwent LDG (n=809) were matched to patients who underwent RDG (n=232) at a 1:1 ratio, by using a propensity score matching method after stratification for the operative year. The surgical outcomes, such as trends of operative time, blood loss, and complication rate, were compared between the two groups. The RDG group showed a longer operative time (171.3 minutes vs. 147.6 minutes, P<0.001) but less estimated blood loss (77.6 ml vs. 116.6 ml, P<0.001). The complication rate and postoperative recovery did not differ between the two groups. The RDG group showed a longer operative time and similar estimated blood loss compared with the LDG group after 5 years of experience (operative time: 159.2 minutes vs. 136.0 minutes in 2015, P=0.003; estimated blood loss: 72.9 ml vs. 78.1 ml in 2015, P=0.793). In terms of short-term surgical outcomes, RDG may not surpass LDG after a long-term experience with the technique.